2013
DOI: 10.1177/0192513x13507569
|View full text |Cite
|
Sign up to set email alerts
|

Number of Siblings and Social Skills Revisited Among American Fifth Graders

Abstract: Most research on the consequences of the number of siblings highlights their downside-the negative association between sibship size and educational outcomes. But recently scholars have begun to understand the potential benefits of siblings, with some research indicating that kindergartners are more socially adept when they have at least one brother or sister. We expand this line of inquiry by studying fifth graders, a point where sufficient school-based peer interactions have occurred to potentially eliminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
(52 reference statements)
2
45
1
3
Order By: Relevance
“…To further understand the influence of siblings on the development of social competence, we examined associations between sibling characteristics and child gender in relation to changes in children's social skills over 1 year. Previous research has shown that children with a sibling gained more social skills between kindergarten and fifth grade than children without siblings (Downey et al, ). However, our results suggest that the gender of the sibling may be particularly important for social skill development.…”
Section: Discussionmentioning
confidence: 97%
“…To further understand the influence of siblings on the development of social competence, we examined associations between sibling characteristics and child gender in relation to changes in children's social skills over 1 year. Previous research has shown that children with a sibling gained more social skills between kindergarten and fifth grade than children without siblings (Downey et al, ). However, our results suggest that the gender of the sibling may be particularly important for social skill development.…”
Section: Discussionmentioning
confidence: 97%
“…In retrospect, the fact that these teenagers were acquiring some education could prove to be a positive factors for their psychosocial resilience. Downey, Condron and Yucel (2015) contend that educated people are more resilient and better able to deal with psychosocial stressors than the uneducated.…”
Section: Demographicsmentioning
confidence: 99%
“…Sibling interactions are believed to be useful for developing social skills and relations with peers (Whiteman et al, 2011), and having fewer siblings-or no siblings at all-can have grave behavioral consequences (Downey et al, 2015). For instance, Cameron et al (2013) describe Chinese only-children as less trusting, less trustworthy, more risk-averse, less competitive, more pessimistic, and less conscientious than their counterparts who have siblings.…”
Section: Sibship Size In the Intergenerational Transmission Of Inequamentioning
confidence: 99%
“…Further, children with coresident siblings spent the majority of their discretionary time in activities with their siblings (Dunifon et al, 2017). Growing up without siblings goes along with fewer social skills during childhood (Downey et al, 2015). Siblings also bear importance beyond childhood, as they are typically the longest-lasting family relationship in an individual's life (Dunifon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%